On research of new surface forms as applied to structures of diverse purpose - A L Podgorniy; E A Grinko; N A Solovey (RUDN Journal of Engineering Research, 2013)
The state of affairs in the field of research of new surface forms used as building and machine structures in Russia and Ukraine is analyzed. It is emphasized that well-known geometricians must keep up the interest of young peoples to spatial thin-walled structures.